Synthesis of Amorphous Conjugated Copolymers Based on Dithienosilole-Benzothiadiazole Dicarboxylic Imide with Tuned Optical Band Gaps and High Thermal Stability - Ary R. Murad; Elham M. A. Dannoun; Shujahadeen B. Aziz; Ahmed Iraqi; Sozan N. Abdullah; Muaffaq M. Nofal; Ranjdar M. Abdullah (Applied Sciences, 2021)
Two alternating copolymers of dithienosilole (DTS) were designed and synthesized with small optical band gaps, flanked by thienyl units as electron-donor moieties and benzothiadiazole dicarboxylic imide (BTDI) as electron-acceptor moieties. The BTDI moieties were anchored to two different solubilizing side chains, namely 3,7-dimethyloctyl and n-octyl chains. An analysis of the effect of the electrochemical, optical, thermal, and structural characteristics of the resulting polymers along with their solubility and molecular weight is the subject of this paper. The Stille polymerization was used to synthesize PDTSDTBTDI-DMO and PDTSDTBTDI-8. The average molecular weight of PDTSDTBTDI-DMO and PDTSDTBTDI-8 is 14,600 and 5700 g mol−1, respectively. Both polymers have shown equivalent optical band gaps around 1.4 eV. The highest occupied molecular orbital (HOMO) levels of the polymers were comparable, around −5.2 eV. The lowest unoccupied molecular orbital (LUMO) values were −3.56 and −3.45 eV for PDTSDTBTDI-DMO and PDTSDTBTDI-8, respectively. At decomposition temperatures above 350 °C, both copolymers showed strong thermal stability. The studies of powder X-ray diffraction (XRD) have shown that they are amorphous in a solid-state.